QOL-17. ERRORS ON BEDSIDE TESTING OF ANTI-SACCADES MAY PREDICT COGNITIVE DYSFUNCTION. Issue 2 (22nd June 2018) - Khan, Raja; Merchant, Thomas; Russell, Kathryn; Sadighi, Zsila; Ashford, Jason; Conklin, Heather
Abstract: Anti-saccade is a voluntary contraversive rapid eye movement that is produced exactly opposite to a presented target. It involves inhibition of a reflexive target seeking saccade and voluntary production of a counter saccade. Abnormalities on anti-saccade tests associate with impaired attention and processing speed (PS), but testing anti-saccades requires cumbersome laboratory procedures. We have developed a bedside method to test anti-saccades that takes 3 minutes to complete. We aimed to test if errors on bedside testing of anti-saccades will associate with impaired attention, impulsivity and PS. Seventy-three consecutive participants (ages 5-17) on our craniopharyngioma protocol of proton therapy were evaluated over 1-3-time points. A total of 115 data points were available. Conners' Continuous Performance Test II was used to measure sustained attention and subsets from the Wechsler Intelligence Scales were used to measure PS and working memory. In univariate generalized estimating equation (GEE) analyses, ≥ 20% error rate on anti-saccade test associated with impairment of PS (p=0.001), attention (p=0.03) and impulsivity (p=0.01). Working memory, age at testing, and time point in treatment did not associate with anti-saccade errors. In a multivariable logistic GEE model including PS, attention, and impulsivity, only increased impulsivity (p=0.04) remained significantly associated with ≥ 20% anti-saccade error rate. Our data suggests that for children with brain tumors, bedside measurement of anti-saccades may identify those with impaired attention, impulsivity and PS. These children may then be assessed with formal neuropsychological testing. Anti-saccades testing, if confirmed in validating studies, may become a useful tool in resource limited settings.